Urban temperature analysis and impact on the building cooling energy performances: an Italian case study - Michele Zinzi; Carlo Romeo; Emiliano Carnielo; Alessandro Mangione (Renewable Energy and Sustainable Development)
Climate changes and urban sprawl are dramatically increasing the heat island effect in urban environments, whatever the size and the latitude are, affecting these latter parameters the effect intensity. The urban heats island is a phenomenon observed since the last decades of the XIX century but demonstrated at large scale only one century later, characterised by the increase of air temperature in densely built urban environments respect to the countryside surround cities. Many studies are available, showing urban heat island intensities up to 12°C. This thermal stress causes social, health and environmental hazards, with major consequences on weaker social classes, as elderly and low income people, it is not by chance that survey demonstrated the increase of deaths in such categories during intense and extended heat waves. This study presents the firs results on the observation of air temperature measures in different spots of Rome, city characterised by a typical Mediterranean climate and by a complex urban texture, in which densely built areas are kept separated by relatively green or not-built zones. Six spots are monitored since June 2014 and include: historical city centre, semi-central zones with different construction typologies, surrounding areas again with various urban and building designs. The paper is focused on the analysis of summer temperature profiles, increase respect to the temperature outside the cities and the impact on the cooling performance of buildings. Temperature datasets and a reference building model were inputted into the well-known and calibrated dynamic tool TRNSYS. Cooling net energy demand of the reference building was calculated, as well as the operative temperature evolution in the not cooled building configuration. The results of calculation allow to compare the energy and thermal performances in the urban environment respect to the reference conditions, usually adopted by building codes. Advice and recommendation of suitable technologies to mitigate such conditions are finally given.